Studi Metalografi Pengaruh Filler Serbuk Zinc Pada Pengelasan Titik Beda Material Antara Aluminium Dan Stainless Steel - Bai Dowi, Makhruf; , Muh Alfatih Hendrawan.,ST.,MT (2017)
Spot welding is a widely used in automotive manufacturing. A dissimilar spot welding is one of welding technology developments which can reduce the weight of vehicles. To join between aluminum and stainless steel, there is still difficult since they have different melting point . This research has been conducted by joining between aluminum with thickness 1,2 mm and stainless steel with thickness 1 mm, and puts 0,05 grm filler zinc in the middle of those parts. This study aims to describe the functions of a filler zinc in dissimilar spot welding. Firstly, chemical composition has been tested by using ASTM A751-0 to know type of the materials, macro and micro structure with ASTM E407-07 to know the physique. Then the parameters of welding are variety such current (6000, 7000, 8000 A) and weld time (0,2, 0,3, 0,4 s). Based on the chemical composition test, the type aluminum speciment is 6019 series, stainless steel is martensite ferrite 430 series, and zinc is ZA-12 series. In the macro structure test, it shows that the increasing of diameter nuggets are related of amount current and weld timing. Beside that, welding using filler zinc have nugget more larger than non-filler, and also its aluminum looks bigger to stainless steel because different conductivity. In the micro structure test, HAZ area shows grain on alumunum becomes smaller, but on the stainless steel the grain become bigger. It happens because a cooling process on alumunum is faster than stainless steel. Meanwhile in the nugget, the grain of a filler zinc can be mixed only with alumunum grain. However, the grain of stainless steel cannot be mixed with alumunum and filler zinc grain.